Percutaneous Reduction of Intra-Articular Posterior Wall Acetabular Rim Fragment: Surgical Technique and Case Series With an Average Follow-Up of 2 Years. Issue 7 (July 2022) - Hadeed, Michael M.; Parry, Joshua A.; Stacey, Stephen; Fader, Ryan R.; Heare, Austin; Mauffrey, Cyril
Summary: Small posterior wall rim fractures are typically stable; however, if incarcerated in the joint, they must be removed. It is possible to reduce the morbidity associated with open approaches by addressing these incarcerated fragments in a percutaneous manner. This allows the restoration of joint congruity and removal of the osteochondral fragment from the joint space. The following report details the surgical technique to accomplish this, and the results of a case series of patients who underwent this technique. The advantages include limiting the morbidity of an open approach. However, the surgeon must be prepared to convert to an open approach if percutaneous removal does not accomplish the goals of surgery—a concentric, stable hip joint.